2021
DOI: 10.1093/nar/gkab1027
|View full text |Cite
|
Sign up to set email alerts
|

The MukB-topoisomerase IV interaction mutually suppresses their catalytic activities

Abstract: The bacterial condensin MukB and the cellular chromosomal decatenase, topoisomerase IV interact and this interaction is required for proper condensation and topological ordering of the chromosome. Here, we show that Topo IV stimulates MukB DNA condensation by stabilizing loops in DNA: MukB alone can condense nicked plasmid DNA into a protein–DNA complex that has greater electrophoretic mobility than that of the DNA alone, but both MukB and Topo IV are required for a similar condensation of a linear DNA represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…ParC inhibits the MukBF ATPase (21), implying, given the folded conformation of MukB (23,24) and our crosslinking results, that ParC might interpose itself between the MukB hinge and neck regions and that this might disrupt the ATPase cycle, further suggesting that isolated MukB hinge might stimulate the MukBF ATPase in trans . This proved to be the case.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…ParC inhibits the MukBF ATPase (21), implying, given the folded conformation of MukB (23,24) and our crosslinking results, that ParC might interpose itself between the MukB hinge and neck regions and that this might disrupt the ATPase cycle, further suggesting that isolated MukB hinge might stimulate the MukBF ATPase in trans . This proved to be the case.…”
Section: Resultsmentioning
confidence: 83%
“…In order to develop insight into the interactions between MukBEF subunits and the mechanism of inhibition of the MukBF ATPase by the ParC subunit of Topo IV (21), we performed disuccinimldyl glutarate-catalyzed protein-protein crosslinking experiments with MukB alone, MukB and ParC, and MukB and MukF, followed by trypsin digestion and analysis of the cross-linked peptides by mass spectrometry. The crosslinks found between ParC and MukB, MukF and MukB, and selected crosslinks for MukB alone are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop insight into the interactions between MukBEF subunits and the mechanism of inhibition of the MukBF ATPase by the ParC subunit of topo IV ( 24 ), we performed di-( N -succinimidyl) glutarate–catalyzed protein–protein crosslinking experiments with MukB alone, MukB and ParC, and MukB and MukF, followed by trypsin digestion and analysis of the cross-linked peptides by mass spectrometry (MS). The crosslinks found between ParC and MukB, MukF and MukB, and selected crosslinks for MukB alone are displayed in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…MukB and topo IV are often found in the same locations on the chromosome ( 21 , 22 , 23 ). We have shown that when in a stoichiometric complex together, MukB and topo IV inhibit the catalytic activities of each other: ParC inhibits the ATPase activity of MukB, whereas MukB inhibits DNA transport segment trapping and DNA cleavage by topo IV ( 24 ), suggesting that any ATP-dependent DNA manipulation catalyzed by MukBEF is modulated by topo IV.…”
mentioning
confidence: 99%